A dual sgRNA-directed CRISPR/Cas9 construct for editing the fruit-specific β-cyclase 2 gene in pigmented citrus fruits - Salonia, Fabrizio; Ciacciulli, Angelo; Pappalardo, Helena Domenica; Poles, Lara; Pindo, Massimo; Larger, Simone; Caruso, Paola; Caruso, Marco; Licciardello, Concetta (Frontiers in Plant Science, 2022)
CRISPR/Cas9 genome editing represents a modern biotechnological approach used to improve plant varieties, modifying only one or few traits of a specific variety. This technology cannot be easily used for improving fruit quality traits in citrus, due to the lack of knowledge of key genes, the long juvenility, and the difficulty in regenerating whole plants of specific varieties. Our aim is to use a genome editing approach to produce citrus plantlets whose fruits will contain both lycopene and anthocyanins. So, in this work, we present a dual single guides RNA (sgRNAs)-directed genome editing approach used to knockout the fruit-specific beta cyclase 2 gene, responsible for the conversion of lycopene to beta-carotene. By using this strategy, the gene is targeted by two sgRNAs simultaneously to create a large deletion, as well as to induce point mutations in both sgRNAs. EHA105 strain of Agrobacterium tumefaciens was used to transform five different anthocyanin-pigmented sweet oranges, belonging to Tarocco and Sanguigno varietal groups, and ‘Carrizo’ citrange, a citrus rootstock, used as a model for citrus transformation. Among the 58 plantlets that were sequenced in the target region, 86% of them were successfully edited. The most frequent mutations were deletions (from -1 to -74 nucleotides) and insertions (+1 nucleotide) in all citrus varieties. Moreover, a novel event was identified in six plantlets, consisting in the inversion of the region between both sgRNAs. For 20 plantlets, in which a single mutation occurred, we may exclude chimeric events, supported by the amplicon sequencing of apical shoots, which resumes all the meristem layers. Plantlets did not show an altered phenotype in the vegetative tissues. To our knowledge, this work represents the first example of the use of a genome editing approach to potentially improve citrus fruit qualitative traits.